Inovasi Metode Pembelajaran Pendidikan Sejarah untuk Generasi Milenial - Risdam Habibi Hasibuan; Rahmi Seri Hanida (Keguruan, 2023)
This article discusses the need for innovative teaching methods in history education that are suitable for the millennial generation. This emphasizes the importance of incorporating technology-based learning, such as mobile applications, e-learning platforms, and social media, to make history education more engaging and interactive for the millennial generation. The use of data visualization, virtual field experiences, and an inclusive approach to historical and cultural perspectives are also emphasized. The goal of history education is to provide students with the critical, analytical, and historical literacy skills necessary to understand the modern world. The curriculum should focus on competencies that prepare future generations to compete effectively. Blended learning, which combines face-to-face and online learning, is considered an effective solution in education today. Innovative history teaching methods, such as interactive technology, project-based learning, collaborative learning, digital resources, and multicultural approaches, can help millennials better understand history in the digital era.